Preparing nurses for the 21st century: re-envisioning nursing education and practice in Nigeria (2013)
The paper explores the current situation and future development of nursing education and practice in Nigeria and their influence on health care. This is necessitated due to the significant advances in biomedical science and in the complexity of health care, coupled with observed shortage of nurses and the numerous reports of unsafe and poor quality of patient care, which have served as precursors to the concerns about nursing education and nursing practice in developed parts of the world sincerely twentieth century. This move was initiated and led by American Association of College of Nursing since year 2000. However, stake holders of Nursing profession in Nigeria are yet to take this initiative, which have direct implications for both nursing education and nursing practice in Nigeria, hence the need for this advocacy paper. Major issues and challenges in this regard are discussed with some suggestions on the way forward